Dimensions of Donation Preferences: The Structure of Peer and Income Effects - Michalis Drouvelis; Benjamin M. Marx (Center for Economic Studies and ifo Institute (CESifo), 2019)
Charitable donations provide positive externalities and can potentially be increased with an understanding of donor preferences. We obtain a uniquely comprehensive characterization of donation motives using an experiment that varies treatments between and within subject. Donations are increasing in peers' donations, past subjects' donations, and bonus income. These findings of peer and income effects do not extend to earned income, anonymous donations, or peers' donations of bonus income. A model of an uncertain social norm for giving can explain the patterns here and in several strands of past research. Estimation of the model reveals substantial heterogeneity in subjects' adherence to the norm and perceptions of its form. Correlations between these dimensions of preferences are such that charities with perfect information could increase net revenue using targeted give-aways to certain donors. A simpler fundraising strategy using only the social dimension of donor preferences increases donations by 30 percent.
Keywords: D01; D64; A13; 330; charitable; donation; altruism; warm glow; social preferences; peer effects; experiment